The effects of ultrasound-assisted extraction on polyphenolics compounds obtained from Physalis angulata using response surface approach - Naira Carniel; Rogério Marcos Dallago; Denise Bilibio; Anderson Luiz Nunes; João Paulo Bender; Wagner Luiz Priamo (Acta Scientiarum: Technology, 2018)
Total polyphenols content (TPC), including flavonoids (rutin, mangiferin and kaempferol) and phenolic acids (gallic, caffeic and ellagic acid) from Physalis angulata were recovered by Ultrasound-Assisted Extraction and quantified by UV–vis and HPLC analysis. Process parameters were assessed through a Central Composite Rotatable Design (CCRD) and a model with regression coefficient equal to 0.9640, was used to establish the optimum conditions together with its respective response surfaces. The increase of ethanol percentage and solid-liquid ratio promoted a decrease on TPC but, on the other hand, the increase in the temperature led to an increase in the extraction of these compounds. Experimental results indicated a maximum amount of total polyphenols of 1.039 mg Gallic Acid Eqivalent (GAE) g-1 of extract, 104.88, 4.04, 8.37, 58.28, 13.26 and 1.87mg.L-1 for gallic acid, caffeic acid, ellagic acid, rutin, mangiferin and kaempferol, respectively.